Characterisation of Asphalt Mixes with Recycled Asphalt Pavement - Malekzehtab, Hassan (Curtin University, 2016)
This thesis has characterised two typical Western Australian hot asphalt mixtures containing recycled asphalt pavement(RAP) material in many aspects; dynamic modulus, moisture susceptibility, fatigue life, resilient modulus, marshal properties and rutting resistance. It also, examined their binder properties and the methods to predict them. Moreover, it suggested methods to anticipate the dynamic modulus of the mixtures base on basic mixture’s parameters. Next, it comments on the limits of using RAP in the studied asphalt mixtures.